On the changes and ammendments to the Law on Protection of the Population from Contagious Diseases: What novelties does the so-called corona law bring - Milić Ivan D. (University of Novi Sad, Faculty of Law, 2021)
The National Assembly of the Republic of Serbia has adopted changes and ammendments to the Law on Protection of the Population from Contagious Diseases twice in the year 2020. The main goal of the author is to demonstrate that the adopted changes and ammendments are a "clear indicator" that certain measures adopted in order to stop and slow the spread of the contagious disease COVID-19 were without legal basis.